Effect of shear stiffening gel rheology on its Kevlar fabric reinforced composite under low-velocity impact. Issue 2 (June 2022) - Zhao, Feng; Chen, Heng; Gu, Han; Jiang, Qian; Lu, Zhenqian; Wu, Liwei
Shear stiffening gel (SSG) with significant shear stiffening effect overcomes the problems of fluid volatilization and particle deposition, and exhibits a wide range of application prospects in intelligent protection. In this work, SSG with different rheological properties were manufactured by mechanical blending and crosslinking and coated on Kevlar fabric. The dynamic rheological properties of SSG and the low-velocity impact resistance of Kevlar/SSG composites were investigated, and the coupling mechanism between SSG and Kevlar fabric was analyzed. The results reveal that the storage modulus of SSG increases by 3–6 orders of magnitude when shear frequency ranges from 0.1 to 100 Hz, and the highest storage modulus reached 2.53 MPa. The impact deformation of the composite is reduced after SSG stiffening, and the infiltration of SSG inside the fabric also prevents fibers pull-out during the impact process. By synergizing the performance of SSG and Kevlar fabric, the optimal single-layer T280 composite can absorb up to 70.21% of the impact energy, reaching the energy absorption efficiency of 0.5 J/g. The process optimization and rheological design provide a theoretical foundation to further enhance the impact resistance performance.